1997
DOI: 10.1002/bjs.1800840912
|View full text |Cite
|
Sign up to set email alerts
|

Prospective placebo-controlled randomized trial of lexipafant in predicted severe acute pancreatitis

Abstract: These results suggest that lexipafant may be a useful adjunct to full supportive care in the early management of patients with severe acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…At that time it was believed reasonable to use the development of MODS as a study end point. Unfortunately, the two larger UK studies of lexipafant in acute pancreatitis both found that 70% of patients who developed MODS had evidence of this at admission to hospital [3,11]. Not only did this render much of the effort in carrying out these trials futile, it challenged the perception that patients with severe acute pancreatitis develop MODS over a 48-to 72-hour period after admission.…”
Section: Time Of Onset Of Mods In Acute Pancreatitismentioning
confidence: 93%
See 1 more Smart Citation
“…At that time it was believed reasonable to use the development of MODS as a study end point. Unfortunately, the two larger UK studies of lexipafant in acute pancreatitis both found that 70% of patients who developed MODS had evidence of this at admission to hospital [3,11]. Not only did this render much of the effort in carrying out these trials futile, it challenged the perception that patients with severe acute pancreatitis develop MODS over a 48-to 72-hour period after admission.…”
Section: Time Of Onset Of Mods In Acute Pancreatitismentioning
confidence: 93%
“…These figures are in keeping with results from prospective clinical trials reported from UK and European centres. In the UK multi-centre trial of lexipafant [3], 40% of deaths occurred within the first week, and early mortality in two single-centre studies from the west of Scotland was identical [10,11].…”
Section: Mods and Mortalitymentioning
confidence: 99%
“…Early identification of severely ill patients is helpful in order to insure both rapid and appropriate treatment; endoscopic sphincterotomy has become more widely applied for the management of severe gallstone-induced acute pancreatitis [1,2] and other specific therapies are available or being developed [3][4][5]. The earlier these treatments are applied, the more effective they will be in the prevention of complications.…”
Section: Introductionmentioning
confidence: 99%
“…This condition however is not very useful in clinical practice and is limited to the use of gabexate mesilate for prevention of ERP-induced acute pancreatitis. Lexipafant, a potent antagonist of platelet-activating factor (PAF), was a new promising candidate probably effective in experimentally induced pancreatitis in rats, as well as in an initial pilot study in humans showing reduced pancreatic and extrapancreatic inflammation as well as a reduction in organ complications [88]. However, in a recent large unpublished multicenter study, a beneficial effect was not confirmed [89].…”
Section: Causal Treatmentmentioning
confidence: 87%